2023
DOI: 10.1186/s12884-023-05576-8
|View full text |Cite|
|
Sign up to set email alerts
|

“Because it eases my Childbirth Plan”: a qualitative study on factors contributing to preferences for caesarean section in Thailand

Abstract: Background Although caesarean section (CS) rates have increased rapidly in Thailand, the upward trend is not supported by significant maternal or perinatal health benefits. The appropriate use of CS through QUALIty DECision-making by women and providers (QUALI-DEC project) aims to design and implement a strategy to optimize the use of CS through non-clinical interventions. This study aimed to explore the factors influencing women’s and health professionals’ preferences for CS delivery in Thaila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The marginalized population reported here are receiving cross-border care in a setting with high and growing rates of caesarean delivery in Thailand. Meanwhile, Myanmar is in the midst of another coup which seriously and negatively impacts access to maternal health services including contraception and delivery services, with implications for future safety for a woman with a uterine scar [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The marginalized population reported here are receiving cross-border care in a setting with high and growing rates of caesarean delivery in Thailand. Meanwhile, Myanmar is in the midst of another coup which seriously and negatively impacts access to maternal health services including contraception and delivery services, with implications for future safety for a woman with a uterine scar [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with another study [ 28 ] among Thai mothers which also found that willingness to pay for delivery fees led to an increased likelihood of cesarean delivery. While our study did not examine factors contributing to patients’ preferences for cesarean delivery, a recent qualitative study among Thai women revealed that the reasons for such action were largely centered on the convenience of cesarean delivery to schedule birth, avoid labor pain, and ensure perceived safe childbirth [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These finding are consistent with the results of previous studies in similar context [ 13 , 36 38 ]. Most pre-labour CS were performed in Argentina and Thailand, countries where women’s preference for a pre-labour CS seems to be marked, revealed by women and accepted by obstetricians [ 39 – 41 ]. This is correlated with our findings which show that crude odds ratios of intrapartum CS are usually equal or smaller than those of pre-labour CS and that more than 30% of pre-labour CS were performed on maternal request in our sample.…”
Section: Discussionmentioning
confidence: 99%